SEMIOTIKA FERDINAND DE SAUSSURE PADA SASTRA LISAN LAMPUNG SESIKUN BUMBANG AJI APPENG LABUHAN RATU LAMPUNG TIMUR - Astria, Astria; Enjelita, Aulia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
One of the elements that enriches Lampung's culture is literary works conveyed orally. Literature is an inseparable element of social life. Its existence reflects the creativity and work of a community. Based on its method of delivery, literature can be divided into two types: oral literature and written literature. This study examines the oral literature Sesikun Bumbang Aji Appeng from the Lampung Timur community by applying the semiotic theory developed by Ferdinand de Saussure, which focuses on the interaction between the signifier and the signified. The purpose of this research is to identify the symbolic meanings and cultural values embedded in the oral literary work. The study employs a qualitative descriptive method with an interpretative approach to analyze the meanings of linguistic signs within the cultural context of the Lampung people. The analysis reveals that each signifier in Sesikun corresponds to a signified that reflects traditional and social values, such as respect for social boundaries symbolized by the selendang (shawl), a spirit of togetherness, courage, openness, and the importance of maintaining relationships and communication. Therefore, Sesikun Bumbang Aji Appeng functions not only as a form of oral literature but also as a cultural sign system that embodies the identity, morality, and life philosophy of the Lampung Timur community.